An Overview of Biblical Hebrew Grammars and Current Trends in Research on Masoretic Accents - Sutton, Lodewyk (Journal for semitics, 2023)
The Masoretic accents are, from different points of view, a neglected field of research. This is mainly because of the way that students of Biblical Hebrew are exposed to the accents in their formation years and to how the functional value of the accents was viewed. In recent years, a new scholarly interest in the accents has developed with a specific focus on the function and value of the accents. This article provides a short overview of some Biblical Hebrew grammars to indicate how these grammars have included and approached the study of Masoretic accents. This will be done by comparing the content of a number of introductory-level grammars as well as intermediate-level grammars. Attention will be given to grammars by South African scholars. After that, a number of conclusions are drawn, and several recent contributions on the topic are considered.